2010
DOI: 10.1080/21513732.2010.509630
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards wild animal conservation: a comparative study of the Yi and Mosuo in China

Abstract: Global wild animal resources are declining due to various pressures, which will greatly affect local biodiversity and ecosystem services. Understanding local people's attitudes towards wild animal conservation in high biodiversity areas is of major importance for conservation efforts. Sampling and questionnaire survey methods were employed to examine people's attitudes toward wild animal conservation in a comparative case study of two minority ethnic groups, the Mosuo (n ¼ 91) and Yi (n ¼ 169) in Ninglang, Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In general, women perceived more importance about /had greater awareness of/ were more willing to contribute their time to this ES type (Briceno and Ravera, 2016;Gao et al, 2014;Mensah et al, 2017;Mudaca et al, 2015;Palliwoda et al, 2017;Swapan et al, 2017;Yang et al, 2010;Zoderer et al, 2016a,b) Some studies do show that men tended to have higher awareness of this ES type Oteros-Rozas et al, 2014;Warren-Rhodes et al, 2011;Yang et al, 2015).…”
Section: Aestheticmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, women perceived more importance about /had greater awareness of/ were more willing to contribute their time to this ES type (Briceno and Ravera, 2016;Gao et al, 2014;Mensah et al, 2017;Mudaca et al, 2015;Palliwoda et al, 2017;Swapan et al, 2017;Yang et al, 2010;Zoderer et al, 2016a,b) Some studies do show that men tended to have higher awareness of this ES type Oteros-Rozas et al, 2014;Warren-Rhodes et al, 2011;Yang et al, 2015).…”
Section: Aestheticmentioning
confidence: 99%
“…Habitat conservation and biodiversity maintenance. Generally speaking, most studies reviewed conclude that women had greater awareness of, were more willing to contribute their time to, or considered habitat conservation and biodiversity maintenance more importantly compared to men (Briceno and Ravera, 2016;Gao et al, 2014;Mensah et al, 2017;Mudaca et al, 2015;Palliwoda et al, 2017;Swapan et al, 2017;Yang et al, 2010;Zoderer et al, 2016a,b). This conclusion was true for all ecosystem types: forest/agroforestry, waterbodies, mangroves and marine areas.…”
Section: Supportingmentioning
confidence: 99%
“…This was illustrated by some respondents' explanatory comments, such as the project supervisor who suggested that gender issues are not relevant to projects concerned with specific wildlife species or to climate change. The respondent was not aware of the growing literature related to genderbased aspects of human-wildlife conflict (e.g., Treves et al 2006;Ogra 2008;Yang et al 2010;Campbell and Alvarado 2011) or climate change (e.g., Cutter 1995;Denton 2002;UNCSW 2008;Terry 2009). Increased levels of collaboration in scholarship and research between wildlife biologists and social scientists could help to address this research gap.…”
Section: Discussionmentioning
confidence: 99%
“…One study in India found gender-based inequities in terms of differentiated vulnerability to attack by wild animals including elephants and leopards, leading women to sustain disproportionate rates of deaths or injuries as compared to men (Ogra 2008). Many studies have found that women and men often hold significantly different views about the importance of wildlife or how conservation should be undertaken at the local level (Kellert and Berry 1987;Hill 1998;Kuriyan 2002;Bauer 2003;Martino 2008;Campbell 2009;Yang et al 2010).…”
Section: Introductionmentioning
confidence: 96%
“…In addition, the respondents expected compensation from the national level [31]. This indicated that the losses caused by wildlife protection and subsequent human-wildlife conflicts were a major threat to wildlife protection [32,33].…”
Section: Relatively Vague Damage Compensation Caused By Wildlife Protmentioning
confidence: 99%